Hubungan Peran Guru Dengan Kesehatan Mental Anak Usia Dini di Kota Mataram - Netasya, Baiq Aprilindea; Astini, Baik Nilawati; Rachmayani, Ika; Gunawan, Gunawan (Indonesian Journal of Elementary and Childhood Education, 2025)
This study investigates the crucial role of teachers in shaping early childhood mental health during the golden age of development. We aimed to determine if a relationship exists between the teacher's role and the mental health of early childhood students in Mataram City. Employing a quantitative correlational approach, data was collected via questionnaires, observation, and documentation from a random sample of 30 kindergarten teachers in Cakranegara District (from a population of 65). Descriptive analysis revealed that the average teacher role score was "good" (3.0), while children's mental health showed "moderate" indications (3.1). However, the Pearson correlation test indicated no significant relationship between the teacher's role and children's mental health (r = -0.004; sig. = 0.984). The study concludes that the teacher's role has not directly influenced children's mental health, possibly due to external factors like the family environment and insufficient teacher training in mental health. We recommend strengthening teachers' capacity in identifying and addressing early childhood mental health issues.